Jeffrey Sachs, (2005). The End of Poverty: Economic Possibilities for Our Time. New York: The Penguin Press. (Book Summary and Book Review) (Global Journal of Management and Business Research, 2014)
Abstract not found
Keywords: clinical economics; corruption; donors funding; international funding policies; economic development; economic policy reforms; information technology